Dental Profiling and Findings of Multiple Jaw Fractures in Traffic Accident Victim: A Case Report - Yunus, Aditia D.; Gultom, Ferry P.; Puspitawati, Ria; Sari, Fitri A.; Prastyo, Eko; Rijaldi, Ferdy; Suripto, Suripto (Universitas Sam Ratulangi, 2024)
Abstract: Motorcycle riders have a high prevalence of accident risks. These accidents can result in severe injuries and can even lead to death. The death prevalence among motorcyclists is three times higher than that of car passengers, six times higher than that of pedestrians, and almost 50 times higher than that of bus occupants. Traffic accidents can cause blunt trauma. High-speed crashes are common in polytraumatized motorcycle crashes and often display facial injuries. In this case report, the authors present a case of an accident with findings of facial trauma to the forehead, nose, cheeks, and multiple fractures of the maxilla and mandible due to a hard object impact. Dental examination revealed post-mortem tooth loss, fractures of the teeth, attrition, root remains, and visible impaction. In conclusion, craniofacial blunt trauma presents with many clinical features. The authors recommend that the finding of such cases be performed further examinations such as X-rays to gain an idea of the possible location of the fracture and to do an autopsy. Keywords: motorcycle accident; blunt trauma; maxillary fracture; mandibular fracture